Adolescent breakfast skipping is associated with poorer academic performance: a school-based study from Hidhabu Abote District, Ethiopia - Dereje Feye; Tesfaye Gobena; Alexandra Brewis; Kedir Teji Roba (BMC, 2023)
Abstract Background Breakfast is regarded as "the most important meal of the day," suggested to positively affect learning in children and adolescent in terms of cognitive and school performance. Yet, studies in LMIC settings are few and show very inconsistent results. Objective To assess the prevalence and correlates of breakfast skipping and its association with school performance among randomly selected in-school adolescents in Hidhabu Abote Wereda, North Shewa Zone, Central Ethiopia. Methods A cross-sectional study was conducted from November to December 2020. A total of 422 participants were selected randomly from high schools of Hidhabu Abote Wereda. Data were entered in to Epiata version 3.1 and exported to SPSS version 24 for analysis. Bivariate and multivariate binary logistic regression analysis identified factors that were significantly associated with the breakfast skipping. Odds ratio along with 95% Confidence interval was estimated to measure the strength of the association and level of statistical significance declared at p-value less than 0.05. Results The magnitude of breakfast skipping was 41.3%, (95% CI (36.6-46.0)]. There was statistically significant association between breakfast skipping and overall academic performance [AOR: 5.18, 95% CI (1.54-7.46)], mathematics performance (3.88, 95% CI (1.34-11.22)], and English language performance scores [2.92, 95% CI (1.38-7.58)]. Being female [AOR = 1.857, 95% CI (1.05-3.27)], household food insecurity [AOR: 2.478, 95% CI (1.36-4.51)], and less maternal education [AOR 1.89, 95% CL (3.38-7.77)] were independently associated with breakfast skipping. The primary reasons given for breakfast skipping were lack of time, lack of appetite in morning, and concerns around weight gain. Conclusion Nearly half of in-school adolescents were skipped breakfast meals, and reportedly in most cases for reasons unrelated to lack of food access. Students who skipped breakfast had lower levels of school performance.